Cell-sized condensed collagen microparticles for preparing microengineered composite spheroids of primary hepatocytes. Issue 19 (7th October 2015) - Yamada, Masumi; Hori, Ayaka; Sugaya, Sari; Yajima, Yuya; Utoh, Rie; Yamato, Masayuki; Seki, Minoru
<x xml:space="preserve">Abstract</x> Cell-sized, highly condensed collagen microparticles were produced, which were utilized to fabricate composite multicellular spheroids of primary hepatocytes.